ANALISIS PENERAPAN KEPEMIMPINAN 360 DI POLRES CIMAHI: Bersyukur; Kepemimpinan 360; kompetensi; Polri; Polres Cimahi - Nasri; Hadi Kristanto; Amril Muhammad (Fakultas Ekonomi Universitas Djuanda, 2022)
The policy of Polri Presisi encourages the leadership of Polri to be not only diligent, but also ready to make decisions quickly, precisely, and professionally. The leadership in Polri should no longer a single fighter, but must build team solidarity through cooperation and synergy. This research wants to get an overview of the application of The 360 Leadership in Polres Cimahi, that is a leadership style that focuses leadership on top, side, and bottom. The research used descriptive qualitative method with the results showing that top leadership is applied through leading ourself to become an excellent leader, manage emotions and time intelligently, lighten the load, have a better performance than before, don’t resist a difficult task or no guide, work above the standard, build good relations with the head. The side leadership is applied through: provide support and assistance, build a team work, find solutions to problems that non-contradictory with organizational rules and external conditions, build up networks with stakeholders, think positively to coworkers, develop creative ideas, and don't think ourself the greatest. The bottom leadership is applied through: keep in touch and visit, remembering the main tasks of the function that must be done, open space for consultation problem solving on work or personal, seek opportunities for competency improvement, give rewards and remind to always be excited and grateful..